Diaries from Isolation. Digital Testimonials' Analysis During COVID-19 Emergency - Jessica Parola; Federica Palmieri; Marco Sallusto Palmiero; Roberta Tofani (Culture e Studi del Sociale)
The research investigates the social effects of the atypical domestic containment situation during the Covid-19 emergency in Italy. The survey, which is placed in a phenomenological perspective, shows how individuals and the community have been able to develop an adaptation or resilience process to the lockdown in order to conform their life to the “new ordinary”, making it real and purposeful. The research process, which was entirely conducted digitally through specific software for qualitative analysis, has developed dynamically, following the Grounded Theory approach. Facebook posts and Instagram audio tracks combined with newspaper articles represent the cases of the research. While on one hand, digitality has allowed an individual the perception of normality by feeling part of a community, on the other it has revealed various forms of digital divide, characterized by different levels of literacy at school, at work and domestically. The social disadvantage does not exclusively concern the digital world but rather on the lockdown that has heightened the systematic exclusion of the most fragile sections of the population.